The Development of Learning Activities in Visual Arts on Painting and Coloring Based on Brain-Based Learning and Cooperative Learning for Grade 6 Students - Maniiam, Phannaphat; Prasertsin, Ujsara (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to compare the learning achievement in the Visual Arts course on painting and coloring for Grade 6 students before and after learning through brain-based learning combined with cooperative learning. Additionally, it aimed to compare students’ artistic creativity skills with the criterion of 70% of the total score. The experimental group consisted of 22 Grade 6 students in the second semester of the academic year 2024 from Wat Mahannapharam School under the patronage of the Royal Family, under the jurisdiction of the Phra Nakhon District Office, Bangkok. The research instruments included eight lesson plans, an achievement test, and an assessment form for evaluating artistic creativity skills in painting and coloring. The statistical methods used for data analysis included percentage, mean, standard deviation, and the Dependent Samples t-test. The research findings revealed that: 1.The post-learning achievement of Grade 6 students who participated in learning activities based on brain-based learning and cooperative learning was significantly higher than their pre-learning achievement at the .01 level of statistical significance. 2.The artistic creativity skills of Grade 6 students who learned through these activities reached 91.02%, which was significantly higher than the established criterion of 70% of the total score at the .01 level of statistical significance. Suggestions from the research results There should be a study of the results of organizing learning activities based on the concept of using the brain as a base together with cooperative learning management with teaching in other subject groups and integrating with various teaching methods, taking into account the content and related objectives, emphasizing the process of creating knowledge by students themselves, which will lead to the application of knowledge to connect with other matters in the future. Keywords: Visual Arts Learning Activities, Brain-Based Learning, Cooperative Learning